The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/arcm.12686
|View full text |Cite
|
Sign up to set email alerts
|

Classification of archaeological adhesives from Eastern Europe and Urals by ATR‐FT‐IR spectroscopy and chemometric analysis

Abstract: Attenuated total reflection-Fourier transform-infrared spectroscopy (ATR-FT-IR) analysis of 100 adhesive samples from different prehistoric composite artefacts, pottery, and amorphous lumps across Eastern Europe and Urals were conducted with the aim to establish a fast analytical screening method for adhesive assignment. The ATR-FT-IR analysis allowed the identification of major chemical components of the adhesive samples that were assigned to three main groups: birch bark tar without major additives, birch ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
(76 reference statements)
2
14
0
Order By: Relevance
“…In 74% of their instances they are associated with aquatic or terrestrial animal fats. There is an almost complete absence (29 of 1,425) of lipid profiles typical of plant resins and tars (where di-or triterpenes are prominent in the extract), perhaps unexpected given the presumed importance of these substances to hunter-gatherers 25,26 . Similarly, only one sample found at Grube-Rosenhof LA 58 (ref.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…In 74% of their instances they are associated with aquatic or terrestrial animal fats. There is an almost complete absence (29 of 1,425) of lipid profiles typical of plant resins and tars (where di-or triterpenes are prominent in the extract), perhaps unexpected given the presumed importance of these substances to hunter-gatherers 25,26 . Similarly, only one sample found at Grube-Rosenhof LA 58 (ref.…”
Section: Articlementioning
confidence: 99%
“…25 Podlachian Museum in Białystok, Białystok, Poland. 26 Research Center for the Preservation of Cultural Heritage, Saratov, Russia. 27 Centre for Baltic and Scandinavian Archaeology, Schleswig, Germany.…”
Section: Reporting Summarymentioning
confidence: 99%
“…There is a significant body of research supporting the widespread use of bitumen in the Fertile Crescent (ex: Connan and van de Velde, 2010; Breu et al, 2022) which predates the introduction of agriculture and pastoralism (Bar-Yosef, 1987;Rosenberg and Chasan, 2021). Nevertheless, in Neolithic Europe, mainly birch bark tar and tree resins were chosen for the same applications (Chen et al, 2022;Rageot et al, 2016Rageot et al, , 2021Urem-Kotsou et al, 2018) although bitumen was still used in southern Italy, where accessible deposits existed (Nardella et al, 2019). Whether newly arrived Neolithic groups developed the technology to produce birch bark tar independently or they adopted it after contacts with local communities is a question still unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…Archaeological investigations into tar production, especially derived from birch bark, span a vast chronology—from the Middle Palaeolithic to the medieval period (Chen et al 2021; Rageot et al 2016; Regert et al 2019; Schenck & Groom 2018; Schmidt et al 2019; Stacey et al 2020). Tar is a plant sub-product typically made from birch bark or pine wood, which appears within the archaeological record as an amorphous residue, either as a lump or associated with a variety of objects including lithic and osseous tools, ceramic vessels and personal ornaments.…”
Section: Introductionmentioning
confidence: 99%
“…Like other organic adhesive products, the preservation of terpenoid tars can be negatively impacted under particular preservation conditions, such as acidic soils (Croft et al 2016); or, in the right conditions, e.g. anoxic or humid conditions, preserved (Chen et al 2021, 13). Experimental work focused on understanding the rate of preservation of different adhesive substances has demonstrated that birch tar survives exceptionally well, slightly better than other adhesives (e.g.…”
Section: Introductionmentioning
confidence: 99%